Physical models of cell motility - Aranson, Igor S. (Biological and Medical Physics, Biomedical Engineering, 2016)
Introduction -- Phase-field Description of Cell Movement -- Role of Substrate Adhesiveness -- Cytoskeletal Waves -- Chemical Signaling -- Efficiency of Cell Motion.